Exploring the Therapeutic Potential of Noncoding RNAs in Alzheimer’s Disease - Tripathi, Siddhant; Sharma, Yashika; Kumar, Dileep (Protein and Peptide Letters, 2024)
Despite significant research efforts, Alzheimer's disease (AD), the primary cause of dementia in older adults worldwide, remains a neurological challenge for which there are currently no effective therapies. There are substantial financial, medical, and personal costs associated with this condition. Important pathological features of AD include hyperphosphorylated microtubule-associated protein Tau, the formation of amyloid β (Aβ) peptides from amyloid precursor protein (APP), and continuous inflammation that ultimately results in neuronal death. Important histological markers of AD, amyloid plaques, and neurofibrillary tangles are created when Aβ and hyperphosphorylated Tau build-up. Nevertheless, a thorough knowledge of the molecular players in AD pathophysiology is still elusive. Recent studies have shown how noncoding RNAs (ncRNAs), including microRNAs (miRNAs), long noncoding RNAs (lncRNAs), and circular RNAs (circRNAs), regulate gene expression at the transcriptional and posttranscriptional levels in a variety of diseases, including AD. There is increasing evidence to support the involvement of these ncRNAs in the genesis and progression of AD, making them promising as biomarkers and therapeutic targets. As a result, therapeutic approaches that target regulatory ncRNAs are becoming more popular as potential means of preventing the progression of AD. This review explores the posttranscriptional relationships between ncRNAs and the main AD pathways, highlighting the potential of ncRNAs to advance AD treatment. In AD, ncRNAs, especially miRNAs, change expression and present potential targets for therapy. MiR-346 raises Aβ through APP messenger Ribonucleic Acid (mRNA), whereas miR-107 may decrease Aβ by targeting beta-site amyloid precursor protein cleaving enzyme 1 (BACE1). They are promising early AD biomarkers due to their stability in cerebrospinal fluid (CSF) and blood. Furthermore, additional research is necessary to determine the role that RNA fragments present in AD-related protein deposits play in AD pathogenesis.
Keywords: lncRNA